2006
DOI: 10.4049/jimmunol.177.7.4818
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL-1 and TNF Receptor Expression and Function by Endogenous Macrophage Migration Inhibitory Factor

Abstract: Macrophage migration inhibitory factor (MIF) has a key role in regulation of innate and adaptive immunity and is implicated in sepsis, tumorigenesis, and autoimmune disease. MIF deficiency or immunoneutralization leads to protection against fatal endotoxic, exotoxic, and infective shock, and anti-inflammatory effects in other experimental models of inflammatory disease. We report a novel regulatory role of MIF in type 1 IL-1R and p55 TNFR expression and function. Compared with wild-type cells, MIF-deficient ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 53 publications
5
61
0
3
Order By: Relevance
“…Alternative mechanisms through which exogenous and endogenous MIF may influence cell responses comprise its binding to the cell surface receptors CD74, CXCR2, and CXCR4 to initiate intracellular signaling (16,17); intracellular interaction with p53, JAB-1/CSN5, or RPS19 (18)(19)(20); and inhibition of MKP-1 (21). In primary newborn monocytes, MIF sustains MAPK activation by microbial products, in line with previous observations in mice and immortalized cell lines showing that MIF activates the p38, ERK1/2, and JNK pathways to mediate prosurvival, proproliferative, and proinflammatory activities (35,36,(56)(57)(58).…”
Section: Discussionsupporting
confidence: 74%
“…Alternative mechanisms through which exogenous and endogenous MIF may influence cell responses comprise its binding to the cell surface receptors CD74, CXCR2, and CXCR4 to initiate intracellular signaling (16,17); intracellular interaction with p53, JAB-1/CSN5, or RPS19 (18)(19)(20); and inhibition of MKP-1 (21). In primary newborn monocytes, MIF sustains MAPK activation by microbial products, in line with previous observations in mice and immortalized cell lines showing that MIF activates the p38, ERK1/2, and JNK pathways to mediate prosurvival, proproliferative, and proinflammatory activities (35,36,(56)(57)(58).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, MIF deficiency suppressed IL-1 and TNF-a-induced mitogen-activated protein kinases activity and cell proliferation in mouse fibroblasts. Reconstitution of an upstream mitogenactivated protein kinase or MIF reversed these affects (110) . Furthermore, MIF impairs p53-dependent apoptosis sustaining activated macrophage lifespan, thus further amplifying the inflammatory response (111) .…”
Section: Macrophage Migration Inhibitory Factormentioning
confidence: 99%
“…In this regard, MIF can inhibit immunosuppressive glucocorticoids, promote secretion of a variety of cytokines including TNF-a, IL-2, IL-6, IL-8, interferon-gg, IL-1b and inhibit IL-10 propagating a pro-inflammatory response (105)(106)(107)(108) . Endogenous MIF regulates innate immunity via up-regulation of TLR-4, IL-1R1 and TNFR expression (109,110) . Roger and co-workers demonstrated that MIF -/ -macrophages were hyporesponsive to lipopolysaccharide and failed to secrete TNF-a and IL-6 due to profound suppression of inhibitor of NF-kB kinaseb/NF-kB activity (109) .…”
Section: Macrophage Migration Inhibitory Factormentioning
confidence: 99%
“…4 This suggests that MIF may be a high-level regulator of immune and inflammatory events that are induced by other factors such as endotoxin and cytokines. 1 Supporting this is that endogenous MIF is necessary for the Toll-like receptor (TLR)-4 expression that is needed for macrophages to respond to endotoxin. 5 Moreover, immunoneutralization of MIF inhibits the elevation of serum levels of interleukin (IL)-6 and TNF-a in sepsis.…”
Section: Introductionmentioning
confidence: 98%
“…1 It appears to participate in multiple autoimmune and inflammatory states, including sepsis, rheumatoid arthritis, acute respiratory distress syndrome (ARDS), glomerulonephritis and enterocolitis. 2 MIF immunoneutralization and MIF gene deficiencies are associated with protection from endotoxic shock and lethality; abrogating MIF activity also significantly reduces inflammation in several experimental models of autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%